ISOLASI DAN IDENTIFIKASI SENYAWA STEROID DARI KULIT BATANG TUMBUHAN ANDONG (Cordyline fructicosa [L] A. Cheval) - Annisa Aisya; Ritson Purba; Saibun Sitorus (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2012)
The isolation of steroid compounds from the bark of Andong plant (Cordyline fructicosa [L] A. Cheval) that come from Samarinda have been done. Their air-dried powdered from bark of Andong plant (Cordyline fructicosa [L] A. Cheval) (250 gram) were extracted by methanol at room temperature (27oC) and fractioned with n-hexane-water (1:1). Separation of steroid compounds in n-hexane fraction by column chromatography with silica gel 60 (35-70 mesh) based on the Isocratic method and produce six fractions, that fractions were 1, 2, 3, 4, 5 and 6 fractions. Fraction 3 gave a blue fluorescent staining that was observed after under UV light and with the Lieberman Burchard produces a green stain, then the fraction 3 was tested for steroid and produces a blue color indicates a positive steroid that has a yield of 0.0536 gram. Purification of the fraction 3 produces greenish-yellow crystals with Rf value of 0.72 with eluent chloroform (100%) while the value of Rf in n-hexane = 0.68 and Rf in ethyl acetate = 0.42. the UV-Vis spectrum of the crystalline isolate results provide absorption at wavelenght of 252 nm, 263 nm and 334 nm. While the result of FT-IR spectrum gives absorption at wave numbers: 689.63; 768.03; 800.79; 901.81; 977.32; 1052.32; 1201.45; 1273.35; 1358.76; 1463.11; 1662.32; 2853.02; 2926.19; 3056.42 and 3456.33. The bark of Andong plant (Cordyline fructicosa [L] A. Cheval) contains steroid compounds.Keywords: Andong (Cordyline fructicosa [L] A. Cheval), Steroid, Isocratic, Isolation